A LITERATURE REVIEW ON RELIGIOSITY IN PSYCHOLOGICAL RESEARCH IN INDONESIA: CURRENT STATE AND FUTURE DIRECTION - Subhan El Hafiz (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
Studies on the concept of religiosity in Indonesia is already popular. However, no study has been conducted to see the direction and trends of this subjectrecently and how the subject of this study able to give a bigger impact in the future. The aim of this study was to assess the trends on the theme of religiosity studies in Indonesia in the last ten years. The method used was literature review using the data obtained from Google Scholar by two keywords in Indonesian i.e